INOVASI JURNALIS DARING DALAM KOLABORASI TIM CEK FAKTA SELAMA PEMBERITAAN PILPRES 2019 - Hapsari, Dian Tri (Master of Communication Science Program, Universitas Diponegoro, 2020)
The development of information through social media gave birth to the phenomenon of decrease quality information with easy spread of hoaxes. This research analyzes the formation collaboration of the fact check team from several elements of the media community such as the Indonesian online Media Association (AMSI), the Alliance of Independent Journalists (AJI), the Indonesian Anti-Defamation Society (Mafindo), and 24 mainstream online medias in Indonesia during the 2019 Presidential Election news. This reserch argues that the collaboration is a diffusion of innovation over the changing digital culture system of Indonesian society. Seeing this phenomenon, this article argues the importance of collaborative innovation among elements of mass media in strengthening mass media institutions as a gatekeeper for reliable information sources and media literacy amid the rapid development of digital news and newsrooms. This qualitative research aims to remind the importance of media activists to continue collaborating in innovation digital space such as the fact check team activities to increase media literacy in the disruption era. The conclusion of this research states that process diffusion of innovation of collaborating fact checking by the media community has changed journalist work to do high quality logic of journalism. Media innovation that promotes data journalism is a main foundation for combating hoax in the digital media in order to establish democratic public sphare.